Analysis of thermal stresses to 2D plane thermoelastic inhomogeneous strip - Abhijeet Adhe; Kirtiwant Ghadle; Uday Thool (Mathematics in Applied Sciences and Engineering, 2023)
This paper deals with study of the plane elasticity of thermoelastic problems for inhomogenous strip. Here, the original problems are reduced to set the governing equations in the volterra integral equations by making the use of direct integration method. Further using the iteration technique the numerical calculations has been performed. The stress distribution obtained and calculated numerically and shown graphically.